Consuming for status among Malaysian working women / Sukjeet K. Sandhu and Laily Paim - K.Sandhu, Sukjeet; Paim, Laily (Universiti Teknologi Mara Selangor, 2016)
This study measures the influence of money attitude, brand consciousness and social status on status consumption among working women in Klang Valley. A total of 200 working women completed the questionnaires which were collected using mall intercept concept. The focus on luxury brand item was narrowed down to three category which were clothings/scarfs, shoes and handbags. The results revealed that brand consciousness has a significant relationship with status consumption. Women who are consciousness about the brands have a higher tendency to engage in status consumption.